Mud volcanism by repeated roof collapse: 3D architecture and evolution of a mud volcano cluster offshore Nigeria. (December 2019) - Dupuis, Matthieu; Imbert, Patrice; Odonne, Francis; Vendeville, Bruno
Abstract: Using 3D seismic data, we document the subsurface architecture of a cluster of 3 mud volcanoes located on the upper continental slope offshore Nigeria. In a background of gently dipping stratified sediments, the subsurface of the cluster contains 8 seismic sequences made of one subcircular syncline, 1–3 km in diameter, and adjoining unstratified units. Synclines flatten out upward through intercalation of unstratified concave-up lenses between stratified units and are eventually filled by a convex-up unstratified lens onlapped by background sediments. The lower boundary of each sequence is a 0.5–1.5 km-deep bowl-shaped unconformity across which high-dip strata rest above truncated low-dip series. We interpret each seismic sequence as a mud volcano system (MVS) sourced from a connected region and evolving through episodes of roof collapse. Three are associated with the surface mud volcanoes and another 4 to fossil ones. Mud volcano systems are dynamic features that record the evolution of: 1) the material extruded from one single connected source region (depletion zone) as it grows downwards and stepwise becomes depleted; 2) the basal unconformity, which joins strata originally separated by material evacuated in the remobilization process; by analogy with salt tectonics, we propose to call it a "mud weld"; 3) the conduits; and 4) the successive collapsed roofs of the depletion zone. The evolution of each mud volcano system in this interpretation records progressive growth of the depletion zone by downbuilding, punctuated by episodes of roof collapse and extrusion. The geometry and evolution of this type of MVS can be interpreted in the light of analogue models of magmatic caldera development: in early stages, the thin roof experiences downsagging while remobilized material is extruded through an axial pipe-like conduit; in later stages the thickened roof undergoes piston-like subsidence, and mud extrusion occurs along the peripheral fault. Highlights: 3D seismic is used to characterize the subsurface architecture of mud volcanoes. The basic architectural motif includes 1 subcircular syncline and unstratified units. Each of these is interpreted as a multiphase mud volcano system (MVS). An MVS records remobilization and extrusion from one connected depletion zone. Convergence of top and base of depletion zone upon extrusion form a "mud weld".